Straddling realities: The urban foundation and social change in contemporary South Africa - Wilkinson, Peter (My University, 1982)
Until perhaps as recently as a year ago, it would have been tempting to construct a 'radical' critique of the Urban Foundation (UF) around the apparent compatibility of the organization's programme with the objectives of the 'Total Strategy' formulated by the government of P.W. Botha. Indeed, elements of such an analysis remain central to the argument that will be advanced here. But since the events of the past year have exposed the deep-seated antipathy of an important section of the government's electoral base towards any attempt at 'meaningful reform', the inadequacy of a critique which simply continues to assert the UF's complicity in 'Total Strategy' must be confronted. After the recent much-heralded 'report back' conference between Botha and leading businessmen fizzled out inconclusively in Cape Town, it would be merely naive to attempt to maintain the notion of an unpvoblematic partnership of 'state' and 'capital' in a joint project aimed at co-opting the black 'middle classes' under the guise of implementing an essentially hollow reform strategy. What I shall be trying to do in this article, therefore, is to shift the analysis of the UFVs role in contemporary South Africa beyond the terms of this now somewhat unproductive polemic. I propose to approach the problem in two stages. In the first place, I want to locate the UF within the framework of the present (November 1981) conjuncture in South Africa by tracing, briefly and somewhat schematically, certain developments bearing on the role of the Foundation during the nearly five years that have elapsed since it was initially set up in December 1976. Secondly, I shall argue that these developments have left the UF in a position in which it is poised between the reality in which it first took shape and the reality of the present, and I shall explore some of the dimensions of the critical strategic choice with which I believe it is now faced. Throughout, in order to keep the length of this article within acceptable limits and to avoid unnecessary references to matters that have received extensive coverage in the press, I will assume a degree of broad familiarity on the part of readers with the more general aims and activities of the UF.
African Studies Seminar series. Paper presented May 1982
Keywords: Social change. South Africa